Search for Minimal Supersymmetric Standard Model Higgs bosons H/A and for a Z′ boson in the ττ final state produced in pp collisions at s√=13 TeV with the ATLAS Detector - Aaboud, M. (2016)
A search for neutral Higgs bosons of the Minimal Supersymmetric Standard Model (MSSM) and for a heavy neutral Z 0 boson is performed using a data sample corresponding to an integrated luminosity of 3.2 fb −1 from proton?proton collisions at s = 13 TeV recorded by the ATLAS detector at the LHC. The heavy resonance is assumed to decay to a τ + τ − pair with at least one τ lepton decaying to final states with hadrons and a neutrino. The search is performed in the mass range of 0.2?1.2 TeV for the MSSM neutral Higgs bosons and 0.5?2.5 TeV for the heavy neutral Z 0 boson. The data are in good agreement with the background predicted by the Standard Model. The results are interpreted in MSSM and Z 0 benchmark scenarios. The most stringent constraints on the MSSM m A ?tan β space exclude at 95% confidence level (CL) tan β > 7.6 for m A = 200 GeV in the m mod+ MSSM scenario. For the Sequential Standard Model, a Z SSM mass up to 1.90 TeV is excluded at 95% CL and masses up to 1.82?2.17 TeV are excluded for a Z SFM of the Strong Flavour Model.